A distorção idade-série na perspectiva da gestão democrática escolar - Ribeiro, Marli Dias (2023)
This thesis presents the results of a research on the age-grade distortion, one of the fundamental elements of the phenomenon of school failure culture, analyzed from the perspective of democratic management, in the Stricto Sensu Graduate Program in Education, research line Education Policy, Management and Evaluation. The overall objective was to analyze the impact of democratic school management as a strategy to mitigate the age-grade distortion in Basic Education, through participant research. The theoretical bases were based on the dialectical-phenomenological conception and critical epistemologies about the educational and school democratic management, and age-grade distortion. An exploratory investigation was conducted with data collection through observation, interviews, document analysis and participatory meetings in two Basic Education schools in the Federal District, involving managers, teachers and students. The data were analyzed through content analysis with thematic categorization. It was concluded that the age-grade distortion is a multifactorial phenomenon present in the educational and school scenario, especially in the final years of elementary school and high school. The discontinuity in public policies precariously serves students and weakens mitigation strategies, which are still based on solutions centralized by the education network. However, it was identified that schools play a decisive role in repairing age-grade distortion by establishing and strengthening a democratic culture based on participation, dialogue with the community and the education network, are committed to mitigating the challenge and building recommendations from participation and dialogue in a democratic and collaborative school and educational environment. It is still possible to overcome a vision of school failure based on biological, behavioral, cultural and social factors, defend and promote a culture and a political-pedagogical choice for democratic management. Schools and communities are notable protagonists in proposing strategies based on a pact signed in democracy, breaking with a "Pedagogy of School Failure". This work is pioneering in proposing a relationship between age-grade distortion and democratic management as a viable alternative, in view of the existing normative support in schools, democratic management and the opportunities for collective construction that can be created in school system.